Students’ Feelings of Safety, Exposure to Violence and Victimization, and Authoritative School Climate - Fisher, Benjamin W. (American journal of criminal justice, 2018)
Although many students feel unsafe at school, few malleable factors have been identified to increase students’ feelings of safety. Drawing on criminological behavior control theories, this study posits authoritative school climate as one such factor. With data from two nationally representative datasets, this study uses path analysis to examine the relationship between authoritative school climate and feelings of safety, as well as the extent to which this relation is explained by exposure to violence and victimization. Across both datasets, a more authoritative school climate was associated with increased feelings of safety at school. Both models also indicated that this relationship was explained in part by reduced exposure to violence and victimization, although the strength of this indirect effect varied across models. These findings suggest that strengthening students’ relationships with adults and increasing the fairness and consistency of rules in the school may both reduce exposure to violence and victimization and help students feel safer at school.